FC GAMMA RECEPTORS IN RESPIRATORY SYNCYTIAL VIRUS INFECTIONS: IMPLICATIONS FOR INNATE IMMUNITY - Jans, Jop (2013)
Respiratory syncytial virus infections are a major burden in infants less than 3 months of age. Newborns and infants express a distinct immune system that is largely dependent on innate immunity and passive immunity from maternal antibodies. Antibodies can regulate immune responses against viruses through interaction with Fc gamma receptors leading to enhancement or neutralization of viral infections. The mechanisms underlying the immunomodulatory effect of Fc gamma receptors on viral infections have yet to be elucidated in infants. Herein, we will discuss current knowledge of the effects of antibodies and Fc gamma receptors on infant innate immunity to RSV. A better understanding of the pathogenesis of RSV infections in young infants may provide insight into novel therapeutic strategies like vaccination.